Generalized herpes zoster and cutaneous metastasis during chemotherapy for non‐small cell lung cancer: A case report - Yasokawa, Naoya (Thorac Cancer, 2020)
Although herpes zoster is known to occur in some patients with lung cancer, generalized (disseminated) herpes zoster is an uncommon form whereby hematogenous dissemination of the virus occurs and leads to the development of widespread cutaneous lesions. Similarly, skin is an uncommon site of metastasis in patients with lung cancer. Here, we report a clinical case of a 53‐year‐old male patient who developed generalized herpes zoster during chemotherapy for non‐small cell lung cancer (squamous cell carcinoma) and subsequently developed cutaneous metastasis of lung cancer after generalized herpes zoster was cured by treatment with intravenous aciclovir. The coincidence of these two conditions, generalized herpes zoster and cutaneous metastasis, in the patient during lung cancer treatment might be associated with an impaired or dysregulated immune system partly due to repeated chemotherapy, indicating a poor prognosis. Close observation and accurate diagnosis of changes in the skin of patients with lung cancer are important when evaluating their immune status and considering their therapy and prognosis.